PEMAKAIAN SAPAAN KEKERABATAN BAHASA ACEH DI KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Safitri, Mukaramah; Munawarah, Intan; Almunadia, Wina (Jurnal Dedikasi Pendidikan, 2025)
This study aims to examine the use of kinship greetings in Acehnese language in Kuta Baro District, Aceh Besar Regency. This study uses a qualitative descriptive approach. The research location is focused on three villages, namely Deyah, Cot Preh, and Cot Beut. The research data are in the form of sentences containing greeting words. The data sources for this study were obtained from 10 informants, each consisting of 2 people in each research location. Data collection was carried out using interview, recording, and note-taking techniques. Data analysis was carried out through several steps, namely reading all data carefully, recording kinship greetings, classifying data based on lineage and marriage, and concluding the results of the study. The results showed that the kinship greeting system in Acehnese language in Kuta Baro District is categorized into two, namely greetings based on lineage and marriage. Forms of greetings based on lineage include greetings for great-grandparents: Syik Tu, Nek Tu; greetings for grandfathers and grandmothers: Syik, Abusyik, Nek, Nyak; greetings for parents: Father, Abu, Abi, Pak, Mak, Ummi, Bunda; and various greetings for children, grandchildren, and siblings. Greetings based on marriage line include greetings for husbands: Lakoe, Linto, Abang; greetings for wives: Inong, Ureung Inong, Adek; and greetings for in-laws, in-laws, and in-laws. These greetings show variations based on gender, age, and position in the family